Improved water-based antirust varnish for steel pipes

A modified water-based steel pipe coating using core-shell acrylic and acrylic phosphate emulsions addresses the issues of slow drying and poor salt spray resistance, providing rapid drying and enhanced corrosion protection.

CN120310355APending Publication Date: 2025-07-15HUNAN JINHUA SCI & TECH GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510550522.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing water-based steel pipe anti-rust varnish has a long drying time and poor salt spray resistance, which cannot meet the requirements of high efficiency in steel pipe processing and long-term corrosion protection.

Method used

Core-shell acrylic emulsion and acrylic phosphate emulsion are combined with specific additives such as PH regulators, defoamers, leveling agents and thickeners to optimize the preparation process to improve drying speed and corrosion resistance.

Benefits of technology

It significantly shortens drying time, improves salt spray resistance, enhances paint film hardness and substrate adhesion, meets the long-term anti-corrosion needs of steel pipes, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses improved water-based anti-rust varnish for a steel pipe. The anti-rust varnish is prepared from the following components in parts by weight: 40 to 60 parts of core-shell acrylic emulsion, 20 to 35 parts of acrylic phosphate emulsion, 0.1 to 0.3 part of a pH regulator, 0.1 to 0.3 part of an anti-flash-rust aid, 0.01 to 0.2 part of a defoaming agent, 0.01 to 0.2 part of a flatting agent, 1 to 4 parts of a coalescing agent, 0.1 to 0.3 part of a thickening agent and deionized water. The water-based steel pipe anti-rust varnish provided by the invention has the characteristics of short drying time, strong salt spray resistance, high paint film hardness and good base material adhesion by compounding the core-shell acrylic emulsion and the acrylic phosphate emulsion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of steel pipe rust-proof coatings, and particularly relates to an improved water-based rust-proof varnish for steel pipes. Background Art

[0002] As a major global steel pipe producer, China has an annual output of up to 80 million tons, accounting for 60% of the world's total output. Steel pipes are widely used in multiple fields such as construction, oil extraction, and pipeline transportation. During the long-distance transportation of steel pipes, to prevent them from being corroded by the environment, it is usually necessary to spray a layer of paint on the outer surface of the steel pipes for protection. Currently, most domestic steel pipe enterprises use oil-based coatings for spraying. With the increasingly strict national requirements for environmental protection and safety, the pollution and safety hazards caused by oil-based coatings no longer meet the requirements of relevant national policies and regulations. Therefore, developing an environmentally friendly steel pipe rust-proof varnish has become an urgent need in the industry.

[0003] Water-based steel pipe rust-proof varnish, as an environmentally friendly coating, has gradually been applied in the market in recent years. However, the drying time of existing water-based steel pipe rust-proof varnishes is generally long, usually requiring 25 - 30 minutes, which cannot meet the high-efficiency requirements of steel pipe processing. At the same time, the salt spray resistance of these coatings is also poor, generally only able to reach a salt spray resistance of 72 - 96 hours, making it difficult to meet the requirements of long-term anti-corrosion. The main reason for these problems is that the resin component of most water-based steel pipe rust-proof varnishes is only acrylic modified resin, and its performance is relatively ordinary, unable to meet the high requirements of fast drying and salt spray resistance. Therefore, the existing technology has defects such as slow drying and poor salt spray resistance, and at the same time, the hardness of the paint film, adhesion to the substrate, and aging resistance also need to be improved. Summary of the Invention

[0004] In view of the above deficiencies of the existing water-based steel pipe rust-proof varnishes, the present invention provides an improved water-based rust-proof varnish for steel pipes, which has the characteristics of short drying time, strong salt spray resistance, high hardness of the paint film, and good adhesion to the substrate.

[0005] To achieve the above object, the embodiments of the present invention adopt the following technical solutions: An improved water-based rust-proof varnish for steel pipes, the rust-proof varnish comprising the following components in parts by weight: 40 - 60 parts of core-shell acrylic emulsion, 20 - 35 parts of acrylic acid phosphate emulsion, 0.1 - 0.3 part of pH regulator, 0.1 - 0.3 part of anti-flash rust additive, 0.01 - 0.2 part of defoamer, 0.01 - 0.2 part of leveling agent, 1 - 4 parts of film-forming aid, 0.1 - 0.3 part of thickener, and deionized water.

[0006] In one embodiment, the pH regulator is selected from N,N-dimethylethanolamine.

[0007] In one embodiment, the defoaming agent is AFCONA-2524.

[0008] In one embodiment, the leveling agent is AKL-L323.

[0009] In one embodiment, the anti-flash rust additive is Raybo-60.

[0010] In one embodiment, the thickener is a polyurethane associative thickener.

[0011] In one embodiment, the preparation step comprises: Add the core-shell acrylic emulsion into a stirring kettle, set the stirring speed to 500-600 r / min, add deionized water and acrylic phosphate emulsion, set the stirring time to 2-5 min, and stir thoroughly to obtain a mixed solution A; Add pH regulator, anti-flash rust additive and film-forming additive to mixed solution A in sequence, set the stirring time to 5-10 minutes to obtain mixed solution B; Add defoamer, leveling agent and thickener to mixed liquid B in sequence, set the stirring speed to 800-1000r / min, and the stirring time to 10-20min to obtain the finished product.

[0012] The beneficial effects of the present invention are that an improved water-based anti-rust varnish for steel pipes is provided, and by adopting the compounding of core-shell acrylic emulsion and acrylic phosphate emulsion, the anti-rust varnish of the present invention can significantly shorten the drying time while maintaining excellent performance, and meet the high efficiency requirements of steel pipe processing; by introducing acrylic phosphate emulsion, the coating can obtain excellent metal adhesion without adding a substrate wetting agent, thereby greatly improving the corrosion resistance of the coating, and the salt spray resistance can reach more than 240 hours; the paint film hardness of the coating is significantly improved, and good adhesion is maintained, meeting the requirements of long-term corrosion protection of steel pipes. The preparation method of the present invention is simple, easy to operate, and suitable for large-scale industrial production. DETAILED DESCRIPTION

[0013] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0014] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention.

[0015] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Although this invention only describes the methods and materials of some embodiments, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of this invention.

[0016] Without departing from the scope or spirit of this invention, various improvements and changes can be made to the specific embodiments of the description of this invention, which will be obvious to those skilled in the art. Other embodiments obtained from the description of this invention will be obvious to those skilled in the art. The description and examples of this application are merely exemplary.

[0017] Regarding the terms "comprising", "including", "having", "containing", etc. used herein, they are all open-ended terms, meaning including but not limited to.

[0018] Unless otherwise specified, the "parts" described in this invention are all by mass.

[0019] Next, the technical solutions in the embodiments of this invention will be clearly and completely described in conjunction with the diagrams in the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, rather than all embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of this invention without creative efforts fall within the scope of protection of this invention.

[0020] An improved water-based anti-rust varnish for steel pipes comprises the following components in parts by weight: 40 - 60 parts of core-shell acrylic emulsion, 20 - 35 parts of acrylic phosphate emulsion, 0.1 - 0.3 part of pH regulator, 0.1 - 0.3 part of anti-flash rust additive, 0.01 - 0.2 part of defoamer, 0.01 - 0.2 part of leveling agent, 1 - 4 parts of film-forming aid, 0.1 - 0.3 part of thickener, and deionized water.

[0021] In this embodiment, the pH regulator is selected as N,N-dimethylethanolamine (i.e., DMEA). DMEA has strong alkalinity and can effectively neutralize acidic substances to keep the pH value of the system stable.

[0022] The defoamer is selected as AFCONA-2524, which is a water-based coating defoamer based on modified silicone in the AFCONA brand. It has excellent defoaming and foam suppression properties, can quickly eliminate the foam in the liquid, and inhibit the regeneration of foam for a long time. It can also act as a leveling agent and has outstanding balance performance in terms of both defoaming and leveling.

[0023] The leveling agent selected is AKL-L323, which is an organically modified polysiloxane with very short repeating units and a very small molecular weight. It moves very fast in the defective paint film area, so it has excellent anti-cratering function and good leveling property; AKL-L323 has no interlayer adhesion problem and does not affect the recoating of the paint.

[0024] The film-forming auxiliary can be selected from one of dipropylene glycol methyl ether, dipropylene glycol butyl ether or alcohol ester 12, and they are all common film-forming auxiliaries.

[0025] The anti-flash rust additive selected is Raybo-60, which is a rust inhibitor in the Raybo brand of the United States. It has excellent anti-flash rust effect, and a very small addition amount can achieve good results.

[0026] The thickener selected is U-601 thickener, which is a high-solid non-ionic polyurethane associative thickener. It has good thickening effect on medium shear viscosity, and at the same time can provide better low shear viscosity. It can provide improved fluidity and storage stability for the system, has excellent resistance to microbial and enzymatic attacks, and can reduce the splashing during brushing in the construction process.

[0027] In this embodiment, the acrylic phosphate emulsion can be prepared by the following method: Add 26.00 g of methyl methacrylate (MMA), 5.00 g of deionized water and 0.55 g of hydroquinone into a four-necked flask, stir well, add 14.20 g of phosphorus pentoxide in 3 portions, control the feeding ratio n(MMA):n(P2O5)=2:1, control the feeding speed to make the reaction temperature not exceed 40 °C. After all the materials are added, raise the temperature to 75 °C for esterification reaction. After reacting for 3.5 h, add 6.00 g of deionized water for hydrolysis. The hydrolysis temperature is 90 °C and the reaction time is 2 h. Then cool down and discharge to obtain the phosphate functional monomer.

[0028] Add 11.70 g of methanol and 23.00 g of toluene into the four-necked flask. When the temperature rises to 65 °C, add 1.10 g of magnesium strip in batches. After reacting for 5 h, raise the temperature to 75 °C. Adopt a semi-continuous dropping process to drop a mixture of 1.20 g of gallic acid and 16.00 g of DMF. After dropping, react for 1 h, then drop 17.00 g of formaldehyde solution and react for 1 h. Cool down to 60 °C, drop 30 g of 4.5% hydrochloric hydroxylamine aqueous solution by mass, control to add it within 1 h, and then keep warm and react for 2.5 h, and cool to room temperature (25 °C). Pour the product into a separating funnel, let it stand for 3 min, and take the lower layer liquid to obtain the rust converter.

[0029] Add 25.6% water (by mass fraction of the total system mass, the same hereinafter), 0.4% OP-10 and 0.7% DBS composite emulsifier, and 4.0% phosphate functional monomer into a four-necked flask. Control the reaction temperature at 60 °C in a water bath and the rotation speed at 5000 r / min. Mix 4.7% MMA, 3.8% BA and 1.0% MAA and drop them into the flask within 45 minutes to obtain a pre-emulsion.

[0030] Put 0.9% OP-10 and 1.7% DBS composite emulsifier, 1.0% sodium bicarbonate, 4% rust converter and 14.0% water into a four-necked flask. Control the water bath temperature at 80 °C and the rotation speed at 2000 - 3000 r / min. At the same time, dropwise add 10 mL of 0.6% APS solution and acrylic acid-based mixed monomers (17.8% MMA + 15.5% BA + 4.1% MAA) and finish dropping within 90 minutes. Finally, dropwise add 20 mL of APS solution and the pre-emulsion simultaneously within 4 hours, raise the temperature to 90 °C and keep the reaction for 1 hour, then cool back to room temperature by reflux to obtain the acrylic acid phosphate emulsion.

[0031] The acrylic acid phosphate emulsion synthesized by the above method has strong corrosion resistance, good drying property itself, complementary performance with the core-shell acrylic emulsion, can obtain excellent metal adhesion in the coating without adding a substrate wetting agent, and greatly improves the corrosion resistance of the coating, with excellent performance.

[0032] In this example, the preparation steps of the rust-proof varnish include: Add the core-shell acrylic emulsion into a stirring kettle, set the stirring speed at 500 - 600 r / min, add deionized water and acrylic acid phosphate emulsion while stirring, set the stirring time at 2 - 5 minutes, and fully stir to obtain a mixed liquid A; Add a PH regulator, an anti-flash rust aid, and a film-forming aid to the mixed liquid A in sequence, and set the stirring time at 5 - 10 minutes to obtain a mixed liquid B; Add an anti-foaming agent, a leveling agent and a thickening agent to the mixed liquid B in sequence, set the stirring speed at 800 - 1000 r / min, and stir for 10 - 20 minutes to obtain the finished product of the water-based rust-proof varnish.

[0033] Preferably, the optimal ratio of the water-based rust-proof varnish is shown in Table 1, and the ratios of each raw material in the above preparation steps of the rust-proof varnish are configured according to the proportion of the optimal example.

[0034]

[0035] To better illustrate that the performance indicators of the waterborne anti-rust varnish provided by the embodiments of the present invention are superior to those of conventional anti-rust varnishes, the following aspects are tested, including: minimum film-forming temperature, film state, drying performance (surface drying), adhesion, hardness, water resistance, temperature resistance variation, neutral salt spray resistance test, damp heat resistance test, and artificial weathering test. Among them, the detection standard for the minimum film-forming temperature is tested in accordance with GB / T9267-2008; the detection standard for the drying performance (surface drying) is tested in accordance with Method B of GB / T 1728-2020; the detection standard for the adhesion is tested in accordance with GB / T 1720-2020; the detection standard for the water resistance is tested in accordance with GB / T 1766-2008, and the evaluation method is adopted in accordance with GB / T 1766-2008; the detection standard for the temperature resistance variation is tested in accordance with JG / T 25-2017; the detection standard for the neutral salt spray resistance test is tested in accordance with GB / T 1771-2007, and the evaluation method is adopted in accordance with GB / T1766-2008; the detection standard for the damp heat resistance test is tested in accordance with GB / T 1740-2007, and the evaluation method is adopted in accordance with GB / T1766-2008; the detection standard for the artificial weathering test is tested in accordance with GB / T 23987-2009, and the evaluation method is adopted in accordance with GB / T 1766-2008.

[0036] The test results of the performance indicators of the waterborne anti-rust varnish in this embodiment are shown in Table 2.

[0037]

[0038] The waterborne anti-rust varnish prepared by the formulation of the optimal example exhibits excellent comprehensive performance. At 55 °C, the surface drying time is only 12 minutes, which is faster than the ≤15 minutes required by the general performance requirements, improving the production efficiency; in addition, the adhesion also reaches level 0-1, and the hardness is grade B, ensuring a firm bond between the paint film and the steel pipe and sufficient hardness, improving the durability of the paint film; the results of the water resistance, temperature resistance variation, neutral salt spray resistance test, damp heat resistance test, and artificial weathering test are all better than or equal to the general performance requirements, showing the excellent performance of this waterborne anti-rust varnish in various harsh environments. Especially in the neutral salt spray resistance test, the comprehensive rating of the protective paint film of the optimal example reaches level 2, which is better than the general requirement of ≤3 levels; in the artificial weathering test, the comprehensive evaluation of the protective paint film of the optimal example is grade 1, which is better than the general requirement of ≤2 levels.

[0039] The present invention uses a core-shell acrylic emulsion and an acrylic phosphate emulsion in combination. The combined properties of the two emulsions are complementary. The main film-forming substance is the core-shell acrylic emulsion, and the secondary film-forming substance is the acrylic phosphate emulsion. Compared with the conventional modified acrylate as the main film-forming substance of synthetic antirust varnish, the core-shell acrylate can significantly improve the mechanical properties of the polymer such as water resistance, abrasion resistance, weather resistance, stain resistance, and adhesion strength, and can significantly improve the salt spray resistance of the latex, thereby endowing the antirust varnish with more excellent stability and durability.

[0040] In order to better illustrate that the method of using a core-shell acrylic emulsion and an acrylic phosphate emulsion in combination provided by this embodiment can make the coating performance more excellent, on the basis that the main film-forming substance is the core-shell acrylic emulsion and the secondary film-forming substance is the acrylic phosphate emulsion, different types and different parts by weight of other waterborne coating additives are added, and the detection data of their minimum film-forming temperature, film state, drying performance (surface drying), adhesion, hardness, water resistance, temperature change resistance, neutral salt spray test, damp heat resistance test, and artificial weathering test are respectively detected.

[0041] There are 17 following examples, and Tables 3 to 5 respectively correspond to the mixing ratio relationships of raw materials with different parts by weight:

[0042] The data results of the above 17 mixing ratios are shown in Tables 6 to 8:

[0043] From the detection data of the performance indicators of adding different types and different parts by weight of other waterborne coating additives in the above 17 experimental examples, it can be seen that the mixing ratio 17 is the optimal mixing ratio, and its drying performance, water resistance, neutral salt spray test, damp heat resistance test, and artificial weathering test are overall better than the experimental results of other mixing ratios.

[0044] Comparative Example 1

[0045] The preparation process is as follows: Add 15.86 g of deionized water to 80 g of GF-B618, control the stirring speed at 500 - 600 r / min, stir for 2 - 3 min, add 0.2 g of DMEA, 1.5 g of dipropylene glycol butyl ether, and 1.5 g of dipropylene glycol methyl ether, stir for 3 - 5 min, then add 0.08 g of AFCONA-2524, 0.1 g of AKL-L323, 0.2 g of KEPERSURF-1200DPM, and 0.3 g of Raybo-60, adjust the speed to 600 - 800 r / min, and stir for 5 - 10 min. After stirring, add 0.26 g of U-601 thickener and stir for 5 min to obtain the coating of Comparative Example 1.

[0046] Performance testing of Comparative Example 1:

[0047] Comparative Example 2

[0048] The preparation process is as follows: Add 15.84 g of water to 45 g of GF-B618, adjust the stirring speed to 500 - 600 r / min, add 0.2 g of DMEA, 1 g of dipropylene glycol methyl ether, 1 g of dipropylene glycol butyl ether, and 0.3 g of Raybo-60 while stirring, stir for 5 - 6 min, add 36 g of 3EA0401W, stir for 5 - 10 min, then add 0.1 g of AFCONA-2524, 0.1 g of AKL-L323, 0.2 g of KEAPERSURF-1200DPM, and 0.26 g of U-601, adjust the speed to 800 - 1000 r / min, and stir for 15 - 20 min to obtain the coating of Comparative Example 2.

[0049] Performance testing of Comparative Example 2:

[0050] The above embodiments are the preferred implementation schemes of the present invention. In addition, the present invention can also be implemented in other ways. Any obvious substitution without departing from the concept of the technical solution is within the scope of the present invention patent.

[0051] In order to make it more convenient for those of ordinary skill in the art to understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements have also been omitted in this application document. Those of ordinary skill in the art should be aware that these omitted elements can also constitute the content of the present invention.

Claims

1. An improved water-based antirust varnish for steel pipes, characterized in that, The rust-proof varnish comprises the following components in parts by weight: 40-60 parts of core-shell acrylic emulsion, 20-35 parts of acrylic phosphate emulsion, 0.1-0.3 part of pH regulator, 0.1-0.3 part of anti-flash rust additive, 0.01-0.2 part of defoamer, 0.01-0.2 part of leveling agent, 1-4 parts of film-forming aid, 0.1-0.3 part of thickener, and deionized water.

2. The improved water-based anti-rust varnish for steel pipes according to claim 1, wherein The pH regulator is selected from N,N-dimethylethanolamine.

3. The improved water-based anti-rust varnish for steel pipes according to claim 1, characterized in that, The defoamer is selected from AFCONA-2524.

4. The improved anti-rust varnish for water pipes according to claim 1, characterized in that, The leveling agent is selected from AKL-L323.

5. The improved water-based anti-rust varnish for steel pipes according to claim 1, wherein, The anti-flash rust additive is selected from Raybo-60.

6. The improved anti-rust varnish for steel pipes according to claim 1, characterized in that, The thickener is selected from polyurethane associative thickener.

7. The improved water-based rust-proof varnish for steel pipes according to any one of claims 1 to 6, characterized in that Its preparation steps include: Adding the core-shell acrylic emulsion into a stirring kettle, setting the stirring speed at 500-600 r / min, adding deionized water and acrylic phosphate emulsion, setting the stirring time at 2-5 min, and fully stirring to obtain a mixed solution A; Sequentially adding the pH regulator, anti-flash rust additive, and film-forming aid into the mixed solution A, setting the stirring time at 5-10 min to obtain a mixed solution B; Sequentially adding the defoamer, leveling agent, and thickener into the mixed solution B, setting the stirring speed at 800-1000 r / min, and stirring for 10-20 min to obtain the finished product.